Implementasi Manajemen Perubahan Dalam Pembangunan Zona Integritas Wilayah Bebas Dari Korupsi (ZIWBK) di KPP PMB: Implementasi Manajemen Perubahan Dalam Pembangunan Zona Integritas Wilayah Bebas Dari Korupsi (ZIWBK) di KPP PMB - Mardiana, Shintia; Tarigan, Djoesept Harmat (FEB Universitas Maritim Semarang, 2024)
In a change towards what is desired, change management is needed to provide stimulus and also a supervisory and control function in each change process. In this case study, KPP PMB succeeded in carrying out development and obtaining the ZIWBK predicate through three change management implementation processes. The first stage, namely Re-freezing, at this stage it is hoped that all stakeholders will be aware of the need for change, on the basis of which they are required to form an organizational structure to make changes along with the work program that will be delivered. The second stage is the change stage, this stage changes begin to be carried out by executing all the work programs that have been created, socialization from change agents is very necessary to communicate the goals and regulations changed by the organization as well as the commitment of all employees in making changes in behavior, mindset and culture . Changes that have been successfully implemented must be maintained according to documented standards and also carried out regular evaluations in accordance with the aim of the last stage, namely refreezing.